Innovative Travel Agency: Outbreak Travel Gear (OTG) - Mahdzar, Mazlina; Zulkifli, Nabila; Zakaria, Muhammad Aniq Anas; Yazid, Muhammad Aidil; Yunus, Muhammad Fahmi; Musa, Luqman Hafiszat (Multidisciplinary Applied Research and Innovation, 2021)
Outbreak Travel Gear (OTG) is a new era of innovative technological product of travel agency (Innovative Travel Agency). This product aims to combat miscommunication that arise for both tourism frontliners and consumers while travelling during this outbreak due to obligation of wearing face mask. OTG is a product where headphones and face shield are combined and designed in a futuristic way with a touch of digital technology. The idea to develop this product arise to provide a genius solution to the travel agency industries especially tour guides to combat miscommunication that happened during the outbreak while still abide to the SOPs. No such product as OTG has been invented and innovate or available in the market. Therefore, this idea of integrating modern technology and innovation will help travel agencies in improving their communication to consumers while using the mask during their service which provides clearer communication. In this new era where practicing social distancing and wearing a face mask is a must, the use of OTG is a necessity and offer convenience to both parties and eliminate the miscommunications.